(untitled) (Rivista Italiana di Filosofia Analitica Junior, 2017)
In this article a major argument by D. Dennett is analysed in order to provide an ultimate argumentation against any possible declination of Cartesian Materialism, meant as an eﬀective theoretical paradigm to frame any issue concerning the problem of consciousness. In order to do so, Dennett formulates an alternative explanation of consciousness, which is supposedly more consistent with the available empirical evidences concerning the way the brain works. This is the Multiple Draft Theory, which the philosopher supports by adopting the colour phi phenomenon, a widely known perceptual illusion, as a major supporting evidence. This phenomenon is extremely relevant to Dennett as it challenges a common intuition about conscious experiences, notably instantiated within the Cartesian Theatre Paradigm both in its materialistic and dualistic version, namely that the temporal order of conscious experiences reﬂects the temporal order of the events in the external world that triggered them. The colour phi phenomenon, however, shows that this is not the case, making a reformulation of the basic notions orbiting around the problem of consciousness necessary to be rethought.